2010
DOI: 10.2140/ant.2010.4.1077
|View full text |Cite
|
Sign up to set email alerts
|

On the minimal ramification problem for semiabelian groups

Abstract: It is now known that for any prime p and any finite semiabelian p-group G, there exists a (tame) realization of G as a Galois group over the rationals ‫ޑ‬ with exactly d = d(G) ramified primes, where d(G) is the minimal number of generators of G, which solves the minimal ramification problem for finite semiabelian p-groups. We generalize this result to obtain a theorem on finite semiabelian groups and derive the solution to the minimal ramification problem for a certain family of semiabelian groups that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…For solvable groups G, one can use Approach II, to obtain upper bounds on m(G) and for some subclasses of solvable groups, the full conjecture, see [2,15,16,20,23,24]. For example, Kisilevsky, Neftin, and Sonn [15] establish the conjecture for semi-abelian p-groups. However, to date, the conjecture is widely open for p-groups.…”
Section: The Minimal Ramification Problemmentioning
confidence: 99%
“…For solvable groups G, one can use Approach II, to obtain upper bounds on m(G) and for some subclasses of solvable groups, the full conjecture, see [2,15,16,20,23,24]. For example, Kisilevsky, Neftin, and Sonn [15] establish the conjecture for semi-abelian p-groups. However, to date, the conjecture is widely open for p-groups.…”
Section: The Minimal Ramification Problemmentioning
confidence: 99%
“…This theorem shows that every finite abelian group arises as the Galois group of a tamely ramified extension of with a minimal set of ramifying primes (which as mentioned in Sect. 1 is already an easy special case of the results in [7] and [8]), with the added feature that the inertia groups for the ramifying primes can be taken to be any collection of cyclic subgroups that minimally generate G , and where the ramified primes are otherwise completely split in the extension.…”
Section: Decomposition Configurations In Finite Abelian Groupsmentioning
confidence: 99%
“…It follows that if a finite group G can be realized as the Galois group of a number field K over having only tame ramification, then is the smallest possible number of primes p that are ramified in K . In [7] and [8] it is shown that all finite nilpotent semi-abelian groups can be realized by such a minimally tamely ramified extension over …”
Section: Introductionmentioning
confidence: 99%
“…The family of semiabelian groups has appeared in many forms in problems that arise from field theory (e.g. geometric realizations [3], [7], [9], generic extensions [9] and the minimal ramification problem [5]). The following notion of a decomposition is used in [3] to characterize semiabelian groups: Definition 2.1.…”
Section: Properties Of Decompositionsmentioning
confidence: 99%
“…Given a p-group G it is an open problem to find the minimal number of primes ramified in a G-extension of Q (see [8]). As a consequence of Minkowski's Theorem this number is greater or equal to d(G), the minimal number of generators of G. In [5], Kisilevsky and Sonn proved this number is exactly d(G) for a family of p-groups denoted by G p and defined as follows: Definition 1.1. Let G p be the minimal family that satisfies:…”
Section: Introductionmentioning
confidence: 99%